Preliminary Study on the Reproduction of Three Rabbitfish Species (Siganidae) in Sopura Bay, Kolaka Regency : - Muhammad Gazali; Sanjaya, M Din Hamdan; , Juhardin; Simanjuntak, Melati Octapian (Jurnal Ilmiah PLATAX, 2026)
This preliminary study investigated the reproductive biology of three rabbitfish species Siganus doliatus, Siganus canaliculatus, and Siganus puellus collected from Sopura Bay, Kolaka Regency, Southeast Sulawesi. A total of 351 individuals were analyzed between September and November 2025 to determine sex ratio, gonad maturity stages, gonadosomatic index (GSI), and length at first gonad maturity (Lₘ). The results showed male-biased populations in S. puellus (1.53:1) and S. doliatus (1.82:1), while S. canaliculatus exhibited a balanced sex ratio (1.01:1). Most individuals were at gonad maturity stages III–IV, indicating active gonadal development during the sampling period, with the spawning peak estimated in late October to November. The Lₘ values differed between species and sexes, suggesting adaptive reproductive strategies, where males generally matured at smaller sizes than females. The highest GSI values were recorded in S. puellus, indicating higher reproductive activity. These findings provide essential baseline data for understanding reproductive patterns and support sustainable management of rabbitfish resources in Sopura Bay